Efektivitas Modifikasi Pembelajaran Penjas Berbasis Permainan Bulutangkis terhadap Peningkatan Keterampilan Motorik Siswa - Ishak, Muhammad; Sahabuddin; Hasanuddin, M. Imran (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2025)
This study aims to examine the effectiveness of physical education learning modifications based on badminton games on improving students' motor skills at SMA Negeri 2 Makassar. The method used was a quasi-experiment with a pretest-posttest control group design. The sample consisted of 60 grade X students who were divided into two groups, namely the experimental group (n = 30) and the control group (n = 30). The research instruments included motor skill tests such as coordination, agility, balance, and muscle strength. The results of the descriptive statistical analysis showed an increase in the average motor skill score in the experimental group from 65.4 (pretest) to 78.6 (posttest), while the control group increased from 64.9 to 69.3. The independent t-test on the posttest produced a significance value of p <0.01, indicating a significant difference between groups. In addition, the paired t-test showed a significant increase in the experimental group (p <0.001), while the increase in the control group was not statistically significant (p = 0.067). These findings prove that badminton game-based learning modification is more effective than conventional methods in improving students' motor skills. The practical implications of these results indicate the need for the implementation of innovative and enjoyable learning strategies in the school environment.